HOW GENSHIN IMPACT ONLINE GAME IMPACTS PLAYER’S ENGLISH SKILL - I GUSTI NGURAH OCTOVA SEVENTILOFA (GANEC SWARA, 2022)
This study is qualitative research that aims to determine the effect of the game Genshin Impact on the English skills of the players. The ability referred to in this study is limited to the ability to write and read. Correspondents in this study were 20 players of the Genshin Impact game between the ages of 16 – 36 years consisting of 19 male players and 1 female player. The method of data collection was done by using a closed interview method. Then, the information collected will then be analyzed in depth and detail using a grounded theory approach to see the relationship between playing Genshin Impact and the players' English (reading and writing) abilities. The results of this study are true that Genshin Impact has an influence on the English skills of the players although it is not significant